Higher Education Reforms and Their Socio-Economic Contexts: Shifting Funding Regimes and Competing Social Narratives. - Kwiek, Marek (My University, 2012)
From a structural perspective of funding and governance, until 2010-2011, Polish universities have remained largely nreformed in the last two decades, following the initial radical changes right after the collapse of communism in 1989: their adaptations to new postcommunist and market realities were much slower than adaptations of other public sector institutions and organizations, including other parts of the traditional welfare state: social assistance, pension schemes, healthcare provision and primary and secondary education. The latter were substantially reformed in the period from the mid-1990s to the mid-2000s. In two decades (1990-2010), higher education system was steered by two new laws on higher education: the 1990 Law, introducing academic freedom and nstitutional autonomy (leading to the emergence of the Polish State Committee for Research in 1991, an independent grant-making agency), and the 2005 Law, adapting the system to the Bologna Process requirements. The core of the system, including its relatively non-competitive funding modes, heavily collegial governance modes, and a complicated, obsolete, multi-level system of academic degrees and academic careers, remained largely untouched until the end of the 2000s. The amendment to the 2005 Law was passed in March 2011 and it is the second stage of the recent wave of higher education reforms, the first implemented in 2010 and consisting of six new laws regulating the functioning of research. Clearly, in the wave of recent reforms and discussions preceding them (2008-2011), Polish universities are viewed by policymakers as “instruments for national policy agendas” (see Olsen 2007: 26-28) and they are only to a limited degree encouraged, through new governance approaches and funding mechanisms, to become more market-oriented.
Keywords: higher education reforms; social narratives; funding regimes; university funding; university governance; Poland; Polish reforms; reforming higher education; academic community; institutionalism; organizational studies; Johan P. Olsen; university models; governance models; 2011 Law